Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1590/s1516-18462009005000058
|View full text |Cite
|
Sign up to set email alerts
|

Medidas orofaciais em adolescentes do estado do Rio de Janeiro segundo a tipologia facial

Abstract: RESUMOObjetivo: veri car se há diferença entre as medidas orofaciais segundo o tipo facial. Métodos: 39 adolescentes leucodermas entre 15 e 17 anos, de ambos os sexos, com dentição permanente e sem queixa ou histórico de tratamento fonoaudiológico. Utilizando um paquímetro digital CE ELECTRONIC mensurou-se a altura do lábio superior, inferior e ltro, terços superior, médio e inferior da face, assim como distância entre canto externo do olho e comissura labial em ambos os lados. Resultados: considerando a variá… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0
7

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 7 publications
1
11
0
7
Order By: Relevance
“…Moreover, in individuals with medium faces, despite showing disproportion between thirds, this aspect is not so exacerbated that can be characterized by the perceptual evaluation, as the relationship with the horizontal plane occurs in a harmonic way, allowing characterizing it as medium. In cases of short face, most individuals have balanced facial thirds, as demonstrated in the study, both being reduced in relation to the horizontal plane 22,23 .…”
Section: Discussionsupporting
confidence: 68%
“…Moreover, in individuals with medium faces, despite showing disproportion between thirds, this aspect is not so exacerbated that can be characterized by the perceptual evaluation, as the relationship with the horizontal plane occurs in a harmonic way, allowing characterizing it as medium. In cases of short face, most individuals have balanced facial thirds, as demonstrated in the study, both being reduced in relation to the horizontal plane 22,23 .…”
Section: Discussionsupporting
confidence: 68%
“…Differences in measures and facial proportions are demonstrated in studies with populations composed of different races 3,4,9,[11][12][13]25,26 . Authors argue that the findings and the variation of measures in the studies may be related to the large Brazilian miscegenation 13 .…”
Section: Discussionmentioning
confidence: 99%
“…The procedures of anthropometry can help the Speech-Language Pathologist to complement the clinical examination, providing information on the characterization of the face as well as reproducible data 11,12,16 .…”
Section: Introductionmentioning
confidence: 99%
“…A similar study with a sample of 39 adolescents aged from 15 to 17 years found significantly higher values for upper lip height (sn-sto) and lower third (sn-gn) in the dolichofacial participants. There was no significant difference in lower lip height (sto-gn), middle face (g-sn) and right (ex-ch) and left sides of the face (ex-ch) 13 .…”
Section: Resultsmentioning
confidence: 84%
“…As such, the results of this study were compared against those from an investigation with adolescents 13 and another with adults 2 .…”
Section: Resultsmentioning
confidence: 99%